1994
DOI: 10.1007/bf01258315
|View full text |Cite
|
Sign up to set email alerts
|

Real-time computational aspects of multiple manipulator systems

Abstract: Abstract. In this paper, we address the topic of numerical computation in a system of multiple manipulators, one which has received scant attention despite a great deal of research in development of control schemes and the proliferation of similar work on single manipulator systems. Different approaches to computations in kinematics, statics and dynamics of multiple manipulator systems are studied and compared. The results show that significant savings in computational count can be achieved through customizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
1997
1997

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Using the best-known modem robot control schemes for force control and multiple robot systems such as resolved acceleration control and hybrid impedance control as guidelines, we have shown that in general a capability of nearly 100 MFLOPS is needed if the control law of choice is implemented in a straightforward manner at 1 kHz frequency [15]. By customizing the system model, this computational demand can be reduced to an acceptable level [15].…”
Section: 1 Design Objectivesmentioning
confidence: 97%
See 2 more Smart Citations
“…Using the best-known modem robot control schemes for force control and multiple robot systems such as resolved acceleration control and hybrid impedance control as guidelines, we have shown that in general a capability of nearly 100 MFLOPS is needed if the control law of choice is implemented in a straightforward manner at 1 kHz frequency [15]. By customizing the system model, this computational demand can be reduced to an acceptable level [15].…”
Section: 1 Design Objectivesmentioning
confidence: 97%
“…By customizing the system model, this computational demand can be reduced to an acceptable level [15]. This procedure involves combining the decomposition of sparse quasi-diagonal matrices into matrices of lower dimensions and the customization technique developed for single-arm robot models.…”
Section: 1 Design Objectivesmentioning
confidence: 99%
See 1 more Smart Citation